Perkembangan Simulasi Korosi – Sebuah Ulasan Ringkas - Syarizal Fonna; Gunawarman Gunawarman; Syifaul Huzni; Ahmad Kamal Ariffin (Jurnal Metalurgi dan Material Indonesia, 2019)
Corrosion is metal loss due to interaction with the surrounding environment. The consequences of corrosion are so damaging that they can have an impact on human casualties. A report from NACE in 2002 has shown that corrosion losses in the United States was about 3.1% of Gross Domestic Product (GDP). This figure was expected to increase in 2016 to over 6.2% of GDP. Overall, the losses caused by corrosion have reached 3-4% of the GDP of the industrialized countries. The numbers are very large and therefore, corrosion control are very important to be implemented. In efforts to control corrosion, research in the area has been widely conducted. Experimental research has played a very important role. However, the development of simulations in the world of corrosion is also very promising. Corrosion simulations are developed based on numerical methods. The commonly used numerical method is the boundary element method (BEM). In subsequent developments, the optimization method has also been used in the case of inverse analysis such as corrosion detection. This paper presents briefly the development of corrosion simulation which has been performed by many researchers in efforts to solve various corrosion cases.